Koji amazake Maintains Water Content in the Left Cheek Skin of Healthy Adults: A Randomized, Double-Blind, Placebo-Controlled, Parallel-Group, Comparative Trial - Enomoto T; Kojima-Nakamura A; Kodaira K; Oguro Y; Kurahashi A (Dove Medical Press, 2022)
Toshihiko Enomoto, Ayana Kojima-Nakamura, Kazuya Kodaira, Yoshifumi Oguro, Atsushi Kurahashi Hakkaisan Brewery Co., Ltd, Minamiuonuma, Niigata, JapanCorrespondence: Atsushi Kurahashi, Hakkaisan Brewery Co., Ltd, 1051 Nagamori, Minamiuonuma, Niigata, 949-7112, Japan, Tel +81 25-788-0910, Fax +81 25-788-0911, Email a.kurahashi@hakkaisan.jpPurpose: Improvement in water content and skin barrier function on human skin is believed to be induced by koji amazake, a non-alcoholic beverage derived from rice fermented by Aspergillus oryzae (A. oryzae). In order to scientifically identify the effects of koji amazake on human skin, we performed a randomized, double-blind, placebo-controlled, parallel-group comparative trial and quantified the content of glucosylceramide (GlcCer) which would be responsible for the effects.Participants and Methods: Healthy adults concerned with their skin dryness were divided into koji amazake (N = 30) or placebo group (N = 30). During this test, the test beverages were ingested at 118 g/day. Their water content and trans-epidermal water loss (TEWL) were measured at 0 week (baseline) and 8 weeks. The content of GlcCer in test beverages was quantified by HPLC-ELSD.Results: In comparison with the placebo group, the water content in the left cheek of individuals in the koji amazake group was maintained for 8 weeks. In addition, changes in water content from the baseline to 8 weeks differed significantly between the koji amazake (0.19) and placebo groups (− 3.98). Unexpectedly, there was no significant difference in the TEWL between koji amazake and placebo group. We analyzed GlcCer in both koji amazake and placebo beverages, which were found to contain 1.35 ± 0.11 and 0.30 ± 0.07 mg/118 g, respectively. The amount of GlcCer in koji amazake was approximately equal to the dosage of plant-derived GlcCer which has the ability to improve water content and TEWL in humans.Conclusion: Present study has shown that intake of koji amazake contributes to maintain the water content only on the left cheek. The content of GlcCer derived from koji amazake was adequate for maintenance of the water content compared to previous reports. Therefore, it was concluded that GlcCer in koji amazake acts as a functional ingredient.Keywords: Aspergillus oryzae, glucosylceramide, koji amazake, water content